Mekanisme Akuntabilitas Sovereign Wealth Fund: Perbandingan antara BPI Danantara dan GPFG Norwegia - Priatna, Azzahra Vinka; Tasman, Annisha Rahmadhila Adha; Velentina, Rouli Anita (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The accountability mechanism in Sovereign Wealth Funds (SWF) is a crucial aspect in ensuring transparency and sustainability in the management of state investment funds. This mechanism is reflected in the implementation of oversight and managerial responsibility within SWFs. BPI Danantara, as Indonesia’s SWF, operates under an internal oversight system involving a Board of Supervisors, an audit committee, and external monitoring from public auditors and relevant state institutions in a decentralized manner. In terms of managerial responsibility, the Business Judgment Rule (BJR) is applied, providing legal protection for managers in investment decision-making, as long as it is conducted in good faith and without negligence. However, this mechanism still poses a significant risk of corruption due to Indonesia’s low Corruption Perceptions Index (CPI) score. Meanwhile, Norway’s Government Pension Fund Global (GPFG) has a stricter oversight structure, with a hierarchical reporting system from Norges Bank Investment Management (NBIM) to the Ministry of Finance and direct supervision by the Norwegian Parliament. Although GPFG does not apply BJR, it has consistently achieved the highest transparency scores and enjoys stronger public trust in its governance. This study aims to analyze the differences in supervisory regulations and managerial accountability between these two institutions.